2016
DOI: 10.3347/kjp.2016.54.4.439
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Spatial Distribution of Toxoplasmosis in Sheep and Goats in North-Eastern Region of Pakistan

Abstract: Toxoplasmosis is a protozoan disease that is caused by Toxoplasma gondii in livestock and humans. Due to its medical and veterinary importance, it is essential to study the seroprevalence of T. gondii infection among humans and animals in various parts of the world. The major objective of this study was to determine the seroprevalence and spatial distribution of toxoplasmosis in small ruminants (sheep and goats) of north-eastern region, Pakistan. A total of 1,000 animals comprising of sheep (n=470) and goats (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
17
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 13 publications
8
17
2
1
Order By: Relevance
“…In goats, the T. gondii infection seroprevalence that we observed was close to that recorded (11.2%) in Pakistan [43], Central Ethiopia (11.6%) [28], northern America (12.1%) [52], and Algeria (13.2%) [19], but was higher than that observed in Morocco (8.5%) [41], South Africa (4.3%) [53], and India (3.8%) [54]. Other studies reported higher seroprevalences than ours, such as those reported in Ethiopia (25.9%) [55], Thailand (27.9%) [56], Tunisia (34%) [49], Pakistan (41.8%) [57], Egypt (41.7% and 44.3%) [58,59], Libya (50%) [26], and Southern Ethiopia (55.18%) [60].…”
Section: Discussioncontrasting
confidence: 62%
“…In goats, the T. gondii infection seroprevalence that we observed was close to that recorded (11.2%) in Pakistan [43], Central Ethiopia (11.6%) [28], northern America (12.1%) [52], and Algeria (13.2%) [19], but was higher than that observed in Morocco (8.5%) [41], South Africa (4.3%) [53], and India (3.8%) [54]. Other studies reported higher seroprevalences than ours, such as those reported in Ethiopia (25.9%) [55], Thailand (27.9%) [56], Tunisia (34%) [49], Pakistan (41.8%) [57], Egypt (41.7% and 44.3%) [58,59], Libya (50%) [26], and Southern Ethiopia (55.18%) [60].…”
Section: Discussioncontrasting
confidence: 62%
“…The current prevalence of T. gondii antibodies found in meats of goats (42.5%) and sheep (35%) from the two abattoirs is similar to that reported in Iran (goats; 48%, sheep; 32.6%) [24] and Pakistan (goats; 42.8%, sheep; 26.2%) [25]. However, the prevalence estimate in the present work is higher than that reported in goats in Myanmar (11.4%) [26], and lower than the estimates in Egypt (62%) [8] and Italy (63.3%) [27].…”
Section: Discussionsupporting
confidence: 81%
“…The overall higher prevalence was recorded in goat when compared to sheep. The similar higher prevalence in g was reported in Pakistan (goat 42.8%, sheep 26.24%) and Egypt (goat 62%, sheep 26%) (Ahmed et al, 2016, Al-Kappany 2018. Contrasting results also reported in Ethiopia (goat 27.6%, sheep 33.7%), Africa (goat 22.9%, 26%) and Tunisia (34.5%, 40.2%) (Tilahunn et al, 2018, Tonouhewa et al, 2017, Lahmar et al, 2015.…”
Section: Discussionsupporting
confidence: 57%